Kas atsakingas už švarius vandenynus? - Bagdonaitė, Gretė; Chaker, Leila Abi (Vilnius University Open Series, 2020)
More and more oceans are polluted by plastic waste emmitted by humans. Unrestricted production and consumption of plastic products have a major negative impact not only on the world’s lungs – the oceans but also on human health. Ocean plastic pollution is caused by human activities, particularly land-based activities. Therefore, this article addresses two key aspects that should be tackled with this pollution problem. First, the article presents the existing international regulation directed against ocean pollution by land-based sources, highlighting its inefficiencies and shortcomings, while suggesting what decisions should be taken on the international scene. Secondly, Secondly, it discusses ways in which the amount of plastic waste generated can be reduced, with positive consequences not only for the ocean ecosystem but also for national economies.